Penerapan Role Play untuk Meningkatkan Keterampilan Berbicara Siswa dalam Pembelajaran Bahasa Inggris di Kelas IX SMP Negeri 1 Bonjol - Karmila, Neni (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
The aim of this study is to address English learning issues, particularly to enhance ninth-grade students' understanding of role play at SMP Negeri 1 Bonjol. The research utilizes a quantitative method, considering the need for assessment criteria in role play learning. The intervention consists of two cycles with two meetings per cycle, encompassing planning, action implementation, observation, evaluation, reflection, and planning phases. Research subjects are ninth-grade students of class IX B at SMP Negeri 1 Bonjol. Findings indicate that the use of role play stimulates students to actively engage in classroom learning. Implementing the role play learning model enhances students' English speaking skills by 20% and achieves a learning completion rate of 75%. In conclusion, the application of the role play learning model minimizes students' speaking errors.